2012
DOI: 10.1016/j.ibiod.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and study of microorganisms from oil samples for application in Microbial Enhanced Oil Recovery

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(124 citation statements)
references
References 37 publications
(78 reference statements)
11
110
0
3
Order By: Relevance
“…In BH broth, isolates IR2, IR4 and MN6 were proved to be potentially adhering to the n-alkanes surface and utilized as carbon sources to form a new biomass (Rojo 2010). Ibrahim et al (2013) and Gudina et al (2012) reported that the B. licheniformis were dominant bacterial strain in oil reservoir and capable to degrade several mercaptans such as 1-decanethiol and 1-dodecanethiol at 55°C (Chebbi et al 2014). In this study, the MN6 was able to perform superior than other strains or mixed consortium in degradation of C 40 .…”
Section: Discussionmentioning
confidence: 61%
“…In BH broth, isolates IR2, IR4 and MN6 were proved to be potentially adhering to the n-alkanes surface and utilized as carbon sources to form a new biomass (Rojo 2010). Ibrahim et al (2013) and Gudina et al (2012) reported that the B. licheniformis were dominant bacterial strain in oil reservoir and capable to degrade several mercaptans such as 1-decanethiol and 1-dodecanethiol at 55°C (Chebbi et al 2014). In this study, the MN6 was able to perform superior than other strains or mixed consortium in degradation of C 40 .…”
Section: Discussionmentioning
confidence: 61%
“…After 1-3-day incubation at 30 °C, morphologically different colonies were re-cultivated in fresh agar plates at least for three times to obtain pure cultures. Purity of isolates was confirmed through Gram staining (Gudiña et al 2012).…”
Section: Isolation Of Oil Degrading Bacteriamentioning
confidence: 99%
“…One of the primary mechanisms of heavy crude oil viscosity reduction is that degradation of heavy oil fractions through microbial activities, and the other one is that the produced rhamnolipid could enhance the stability of oil/water emulsion system, eventually forming oil-in-water [2,4,24]. The high contents of the employed heavy oil fractions resulted in its high viscosity and poor fluidity.…”
Section: Viscosity Reduction Of Crude Oilmentioning
confidence: 99%
“…MEOR makes use of microbial activities and metabolic byproducts to reduce the viscosity and increase the fluidity of crude oil [4]. On the one hand, microorganisms can reduce the oil viscosity by degrading the long-chain saturated hydrocarbons and some of the other heavy oil fractions [5]; On the other hand, microorganisms can produce non-toxic products such as biosurfactants to increase the oil sweep efficiency through changing the reservoirs' physicochemical characteristics [6].…”
Section: Introductionmentioning
confidence: 99%